Analisis Kebijakan Pemberdayaan Guru dalam Meningkatkan Mutu Pendidikan di MTs Swasta Al-Ittihadiyah Mamiyai Medan - Sufni, Nurul; Yasmin, Salsabila; Akmalia, Rizki; Rahayu, Putri; Zulna, Ryan Fazli; Pamungkas, Faturrahman Hendli (FITRAH: International Islamic Education Journal, 2024)
Teacher empowerment policy is a strategic step to improve the quality of education, especially in private schools that face challenges such as teacher shortage and skills mismatch with curriculum needs. The principal's role as a manager and motivator is crucial in formulating policies that support teachers' well-being, competence, and professionalism to achieve optimal quality of education. This study examines the implementation of teacher empowerment policies in improving the quality of education at MTS Al-Ittihadiyah Mamiyai. It uses a descriptive qualitative approach to analyze the strategies, challenges, and impacts of the policy. Teacher empowerment is carried out through an annual training program that includes workshops, seminars, and technical skills enhancement tailored to teachers' professional needs. Collaboration between schools, the Ministry of Religious Affairs, and foundations strengthens this initiative by focusing on improving curriculum mastery, classroom management, and the use of technology. Results show that empowering teachers has significantly improved the learning environment by encouraging innovative teaching strategies, increasing student engagement, and creating a more interactive classroom dynamic. Challenges such as limited facilities, inconsistent supervision, and uneven participation in training programs hinder long-term success. Overcoming these challenges requires a comprehensive approach that involves systematic collaboration among stakeholders. This study confirms the importance of teacher empowerment as a long-term investment in improving educational standards, while identifying areas for further improvement. Abstrak Kebijakan pemberdayaan guru adalah langkah strategis untuk meningkatkan kualitas pendidikan, khususnya di sekolah swasta yang menghadapi tantangan seperti kekurangan guru dan ketidaksesuaian keterampilan dengan kebutuhan kurikulum. Peran kepala sekolah sebagai manajer dan motivator sangat penting dalam merumuskan kebijakan yang mendukung kesejahteraan, kompetensi, dan profesionalisme guru untuk mencapai kualitas pendidikan yang optimal. Penelitian ini mengkaji penerapan kebijakan pemberdayaan guru dalam meningkatkan kualitas pendidikan di MTS Al-Ittihadiyah Mamiyai. Penelitian ini menggunakan pendekatan deskriptif kualitatif untuk menganalisis strategi, tantangan, dan dampak kebijakan tersebut. Pemberdayaan guru dilakukan melalui program pelatihan tahunan yang mencakup pelatihan, seminar, dan peningkatan keterampilan teknis yang disesuaikan dengan kebutuhan profesional guru. Kolaborasi antara sekolah, Kementerian Agama, dan yayasan memperkuat inisiatif ini dengan fokus pada peningkatan penguasaan kurikulum, manajemen kelas, dan penggunaan teknologi.  Hasil penelitian menunjukkan bahwa pemberdayaan guru telah secara signifikan meningkatkan lingkungan pembelajaran dengan mendorong strategi pengajaran yang inovatif, meningkatkan keterlibatan siswa, dan menciptakan dinamika kelas yang lebih interaktif. Tantangan seperti keterbatasan fasilitas, pengawasan yang tidak konsisten, dan partisipasi yang tidak merata dalam program pelatihan menghambat keberhasilan jangka panjang. Mengatasi tantangan ini memerlukan pendekatan komprehensif yang melibatkan kolaborasi sistematis di antara pemangku kepentingan. Penelitian ini menegaskan pentingnya pemberdayaan guru sebagai investasi jangka panjang dalam meningkatkan standar pendidikan, sekaligus mengidentifikasi area yang perlu perbaikan lebih lanjut.